Avaliação e garantia de qualidade dos serviços de saúde mental. - Caldas-de-Almeida, José M (1995)
Evaluation and quality assurance are primary issues in mental health care today. An up-date of current knowledge and experience in this domain is the main objective of this paper. The authors begin by describing the reasons that justify the current interest in this subject, defining concepts and summarizing the most relevant historical antecedents. This is followed by a discussion of the main methodological aspects--basic concepts (particularly those related to structure, process and outcome), specific issues in mental health service evaluation, difficulties in the implementation of evaluation procedures and choice of indicators. Special attention has been given to the most recent developments in mental health service evaluation--namely those related to assessment needs and quality of life measurement. The impact of the regular use of evaluation instruments on the transformation and development of mental health services is also discussed. The contributions that can be made by evaluation procedures to the definition of mental health policies and to overcome mental health service deficiencies are stressed. Finally, the necessity of joining efforts in order to generalize the use of evaluation and quality assurance instruments in the mental health services in this country is pointed out.